Pengaruh Persepsi Harga, Kualitas Pelayanan dan Citra Terhadap Niat Konsumen untuk Word of Mouth dengan Kepuasan sebagai Variabel Mediasi (Survei pada BPJS di Kabupaten Ponorogo) - Dhika Amalia Kurniawan (Al Tijarah, 2016)
Globalization impact on business competition intensifies, resulting in the exchange of goods and services flow freely in various areas, one of which is the health services. Health care services is one of the important needs for the community. Specifically in this case is the organizer of the Health Insurance Agency (BPJS). The purpose of this study was to determine the effect the perception of price, quality of service and the image of the consumers intention to word of mouth with satisfaction as mediating variables. Data were collected by questionnaire instrument. This model was developed and tested with structural equation model using data collected from 200 patients in Ponorogo. The results showed that before individuals distinguished by the level of information obtained none of the variables that influence satisfaction, better perception of price, quality of service and the image. However, on the one hand satisfaction are variables influential in shaping consumer intentions to WOM. Furthermore, when individuals are distinguished by low and high-level information was obtained that the low level of information, none of the variables that affect the satisfaction of both the perception of price, quality of service and the image. However, on the one hand satisfaction are variables influential in shaping consumer intentions to WOM. Then, based on high-level information indicates that the variable perception of price, quality of service and image effect on satisfaction, while satisfaction are variables influential in shaping consumer intentions to WOM against BPJS services.